Pressure‐induced phase transition and dissociation of PbMoO4. Issue 10 (2nd July 2015) - Huang, Shengxuan; Lai, Xiaojing; Zhu, Feng; Wu, Xiang; Yang, Ke; Qin, Shan
<x xml:space="preserve">Abstract</x> The high‐pressure behavior of PbMoO4 has been studied by in situ synchrotron radiation X‐ray diffraction (XRD) combined with a diamond anvil cell (DAC) up to ∼38 GPa. At room temperature, phase transitions of PbMoO4 from the scheelite structure to the wolframite structure and then to amorphization are detected at ∼8.3 and ∼35 GPa, respectively. Pressure–volume relationships of PbMoO4 are described by the Birch–Murnaghan equation of state, giving V0 = 355.8(3) Å3, K0 = 73(4) GPa, K0′ = 5(1) (third order) for the scheelite‐structured phase and V0 = 166(1) Å3, K0 = 85(4) GPa, K0′ = 4 (fixed) (second order) for the wolframite‐structured phase. When PbMoO4 undergoes the high‐temperature annealing treatment at ∼17.5 GPa, it will dissociate into assembly of the PbO (Pbcm and Z = 4) and PbMo2O7 (P21/c and Z = 4).